Features of scientific papers and the relationships with their citation impact - Yu, Tian; Guang, Yu; Yu, Tian; Yu, Guang (Malaysian Journal of Library and Information Science, 2017)
Yu, T., & Yu, G. (2014). Features of scientific papers and the relationships with their citation impact. Malaysian Journal of Library & Information Science, Vol.19, no. 1: 37-50. It has been proven that several features of scientific papers are relevant to citation impact. The purpose of this paper is to evaluate the role of these features and unravel which features have greater influence on citation impact. A feature space is established to describe four types of scientific papers’ features: features of a paper itself, features of authors, features of published journal, and features of citations. For a group of 676 articles published in 12 journals in the subject category of Information Science & Library Science (IS&LS) in 2007, we analyze quantitatively the difference among high-, medium-, and low-cited papers, and capture their influence on citation impact. The results make it clear that among these four feature types, the quality of a paper and the reputation of authors are the most and the least significant factor affecting the citation impact respectively, and a paper itself has greater influence than the published journal. The findings lay the foundation for the citation impact prediction by using the features of scientific papers.